Diagnosis and Treatment of Chronic Heart Failure in Diabetes of the 2nd Type - M.S. Kultayev; A.Zh. Yesirkepova; A.B. Abdugulova; A.B. Abdykulova; B.Zh. Kanseitova (Journal of Pharmacy and Nutrition Sciences, 2019)
Chronic heart failure (CHF) is an acute medical and social problem relating to the priorities of the national health systems of most countries of the world due to the increasing spread of this syndrome, despite the continuous improvement of treatment. The near future promises only the worsening of the problem: the incidence and prevalence of CHF increases due to the increase in life expectancy. Thus, the need to clarify the features of the diagnosis of CHF in patients with diabetes mellitus and the improvement of their therapy is beyond doubt. The aim of this research is to clarify the frequency of chronic heart failure in patients with diabetes type 2 in the specialized | department of the hospital and the unorganized urban population, to assess the adequacy of its diagnosis and treatment. To achieve this goal, the following tasks: 1. To identify the prevalence of chronic heart failure in patients with diabetes type 2. 2. To assess the level of diagnosis of chronic heart failure in patients with diabetes type 2. 3. To analyze the state of drug therapy in patients with diabetes type 2 in the presence of chronic heart failure. For the first time, the prevalence of CHF in patients with diabetes type 2 mellitus in an unorganized urban population studied.